Technology Transfer: From the ResearchÂ Bench to Commercialization - Gail A. Van Norman, MD; RoÃ¯ Eisenkot, BSci, MBA (JACC: Basic to Translational Science, 2017)
Summary: Progress in medicine hinges on the successful translation of basic science discoveries into new medical devices, diagnostics, and therapeutics. âTechnology transferâ is the process by which new innovations flow from the basic research bench to commercial entities and then to public use. In academic institutions, intellectual property rights do notÂ usually fall automatically to the individual inventor per se, but most often are the property of the institution. Technology transfer offices are tasked with seeing to it that such intellectual property rights are properly managed and commercialized. This 2-part series explores the technology transfer process from invention to commercialization. PartÂ 1Â reviews basic aspects of intellectual property rights, primarily patents and copyrights. Part 2 will discuss the waysÂ in which inventions becomeÂ commercialized through startup companies and licensing arrangements with industryÂ players. Key Words: copyright, intellectual property, patent, technology transfer